Upaya Peningkatan Aktivitas Dan Hasil Belajar Fiqih Melalui Penerapan Metode Gallery Walk Materi Puasa Siswa Kelas VIII-2 MTsS Krueng Raya - Safariah, Safariah (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study was to improve the activities and learning outcomes of jurisprudence on fasting material for students of class VIII-2 MTsS Krueng Raya in the Academic Year 2017/2018. The study was conducted at MTsS Krueng Raya. The method used in this Classroom Action Research is the Gallery Walk learning method. The subjects of this Classroom Action Research are students of class VIII-2 MTsS Krueng Raya. The number of students is 15 students with a total of 8 male students and 7 female students. This Classroom Action Research was conducted in the 2017/2018 Academic Year within a period of 3 months namely from February 2018 to April 2018 in the Even Semester. In each cycle consists of planning, implementation, observation and reflection. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle by using the question instrument (written test). Observation data is done by observing the activeness of students' learning process Data were analyzed by means of percentage statistics. The results showed that an increase in completeness of student learning outcomes from 40.00% in the pre-study increased to 60.00% in the first cycle and increased to 86.66% in the second cycle. Student learning activities have increased from enough categories to be good and good categories increased to very good. The application of Gallery Walk learning method can improve the activities and learning outcomes of Fiqh on Fasting material for students of class VIII-2 MTsS Krueng Raya in the Academic Year 2017/2018.